Energy-Saving Handwasher Design Using Infrared Obstacle Sensor Based On Arduino Microcontroller - Jumrianto Jumrianto; Dewi Purnamasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
The Covid-19 pandemic is over, the good habit of washing hands with soap must be maintained, because it concerns a clean and healthy lifestyle. The unavailability of automatic hand washing devices on the IVET University Campus is a motivation to create an application tool, in its application it will use an infrared obstacle sensor by coding commands through Arduino software. Based on a review of previous research, no one has designed a hand washer device with an energy-efficient infrared obstacle sensor. Utilizing Arduino software and hardware with a current consumption of <0.050 amperes on standby. When operating, this device consumes a current of <0.5 amperes which opens and closes the water tap. The operating voltage of the microcontroller is 5 volts, so this device consumes 2.5 watts of electricity, and if it operates for 1000 hours or for ±41 days continuously without stopping, it only uses 2.5 KWh of electricity and when on standby for 1000 hours this device uses 0.25 KWh of electricity.